2019
DOI: 10.1186/s13071-019-3563-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel praziquantel solid lipid nanoparticle formulation shows enhanced bioavailability and antischistosomal efficacy against murine S. mansoni infection

Abstract: Background Schistosomiasis is responsible for a considerable global disease burden. This work aimed to improve the therapeutic outcome of the only available antischistosomal drug worldwide, praziquantel (PZQ), by incorporating it into a novel carrier, “solid lipid nanoparticles (SLNs)”, to enhance its solubility, bioavailability and efficacy. A simple, cost-effective method was used to prepare SLN-PZQ. Results Compared to market PZQ (M-PZQ), SLN-PZQ was more bioavailabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In this respect, pharmaceutical nanotechnology may address challenges such as inadequate solubility, bioavailability, cellular delivery as well as non-specific biodistribution and rapid clearance of antiparasitic drugs [ 18 , 19 ]. Indeed, drug delivery systems including lipid-based nanocarriers such as liposomes [ 20 ] and solid lipid nanoparticles [ 21 ], niosomes [ 22 ] and silica nanoparticles [ 23 ] were shown to enhance the bioavailability and antischistosomal activity of PZQ. Recently, we demonstrated that entrapment of PZQ into lipid nanocapsules (LNCs) significantly enhanced its antischistosomal activity in a single oral reduced dose of 250 mg/kg in mice [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, pharmaceutical nanotechnology may address challenges such as inadequate solubility, bioavailability, cellular delivery as well as non-specific biodistribution and rapid clearance of antiparasitic drugs [ 18 , 19 ]. Indeed, drug delivery systems including lipid-based nanocarriers such as liposomes [ 20 ] and solid lipid nanoparticles [ 21 ], niosomes [ 22 ] and silica nanoparticles [ 23 ] were shown to enhance the bioavailability and antischistosomal activity of PZQ. Recently, we demonstrated that entrapment of PZQ into lipid nanocapsules (LNCs) significantly enhanced its antischistosomal activity in a single oral reduced dose of 250 mg/kg in mice [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, pharmaceutical nanotechnology may address challenges such as inadequate solubility, bioavailability, cellular delivery as well as nonspecific biodistribution and rapid clearance of antiparasitic drugs (18,19). Indeed, drug delivery systems including lipid-based nanocarriers such as liposomes (20) and solid lipid nanoparticles (21), niosomes (22) and silica nanoparticles (23) were shown to enhance the bioavailability and antischistosomal activity of PZQ.…”
Section: [Le1] [Le1]mentioning
confidence: 99%
“…In this respect, pharmaceutical nanotechnology may address challenges such as inadequate solubility, bioavailability, cellular delivery as well as non-speci c biodistribution and rapid clearance of antiparasitic drugs [18,19]. Indeed, drug delivery systems including lipid-based nanocarriers such as liposomes [20] and solid lipid nanoparticles [21], niosomes [22] and silica nanoparticles [23] were shown to enhance the bioavailability and antischistosomal activity of PZQ. Recently, we demonstrated that entrapment of PZQ into lipid nanocapsules (LNCs) signi cantly enhanced its antischistosomal activity in a single oral reduced dose of 250 mg/kg in mice [24].…”
Section: Introductionmentioning
confidence: 99%